National Accounts Statistics: Analysis of Main Aggregates 2020 - United Nations Department of Economic; Social Affairs (United Nations, 2022)
This publication is the fifty-first issue of this publication which comprises in the form of analytical tables a summary of the principal national accounting aggregates based on official national accounts data for more than 200 countries and areas, covering 1970-2020. It also contains a section on the estimation methods used for compiling data, and is prepared by the Statistics Division of the Department of Economic and Social Affairs of the United Nations in cooperation with national statistical offices. Tables include analysis of data on gross domestic product (GDP) by different structural components. They are classified into: 1) analysis of the level and real growth of total and per capita GDP; 2) analysis of the percentage share of GDP by type of expenditure and gross value added by kind of economic activity; 3) analysis of economic development expressed in terms of real growth of GDP and its components by type of expenditure and gross value added by kind of economic activity; and 4) analysis of price development reflected by implicit price deflators of GDP.